Analisis Inovasi Varian Produk Aci pada Program Kewirausahaan Ciamo: Aci dan Mojito - Putri, Salsa Shabilla; Sari, Aprilia Rofiana; Andriana, Balqis Ersa; Fitriya, Wahyu; Sholicha, Dinia Nikmatus; Suprihandari, Miya Dewi (Jurnal Ekonomi, Pendidikan dan Pengabdian Masyarakat, 2025)
This study aims to analyze the implementation of innovation of tapioca-based product variants in the Ciamo entrepreneurship program, which includes filled cireng, cibay, and mojito, and its influence on the success of student businesses. Using a qualitative approach through a case study design, this study explores the views of consumers from various backgrounds through in-depth interviews with 16 informants in Sidoarjo. The results showed that product innovation received a positive response, especially thanks to the spicy taste, the practicality of the product in frozen form, and the diversity of variants. However, several challenges such as the lack of attractive packaging design, limited digital promotion, and the need for flavor diversification were also found. These findings support the literature that highlights the importance of consumer preference-based innovation and digital marketing in increasing product competitiveness. By strengthening digital marketing strategies, improving packaging design, and developing flavor variants, the Ciamo entrepreneurship program has a great opportunity to become a creative and sustainable student business model.